Analisis Efektivitas Kebijakan Penghapusan Sanksi Administrasi Pajak Kendaraan Bermotor Dalam Upaya Meningkatkan Penerimaan Pajak Daerah Di UPP PKB Jakarta Pusat Tahun 2021 - 2022 - Yani, Indah Fitri; Fiatri, Lisa Arisa; Pribadi, Jiwa (Jurnal Pajak Vokasi (JUPASI), 2024)
This study aims to analyze the effectiveness of the Motor Vehicle Tax Administrative Sanction Elimination Policy in efforts to increase local tax revenue for the period 2021-2022 and to identify challenges in the effectiveness of the Motor Vehicle Tax Administrative Sanction Elimination Policy. The research was conducted at the Central Jakarta Urban Vehicle Tax Office using a qualitataive approach, and the data were obtained through interviews with the respondents and documentation. The research findings indicate that the effectiveness of the Motor Vehicle Tax Administrative Sanction Elimination Policy has been optimally improving local tax revenue from the Motor Vehicle Tax sector. This is evident from the significant decrease in the percentage of Passive Motor Vehicle Taxpayers compared to the previous year and the increase in the percentage of actual local tax revenue realization from the Motor Vehicle Tax sector. However, there were technical challenges faced both internally and externally during the effectiveness. To address these challenges, preventive measures were taken by providing information and guidance to Motor Vehicle Taxpayers to comply with the given regulations, aiming to minimize  errors in the execution.